Efektivitas Modul Pembelajaran Berbasis Proyek sebagai Sumber Belajar Siswa SMK - Leila Fajrie Auddiena Nuriel Fath Albana (Universitas Indraprasta PGRI Jakarta, 2020)
Project-based modules in the learning process in Vocational High Schools are widely used as a learning resource that is applied to improve the quality of student learning. The purpose of this study is to describe the effectiveness of project-based learning modules as a learning resource in improving student learning outcomes in Multimedia Productive subjects. This study uses a quasi-experimental approach with nonequivalent control group design involving 63 students of Muhammadiyah Wonosari Vocational High School. The instruments used were in the form of pretest and posttest questions. Data analysis techniques to determine the significance and effectiveness of this study using the T-Test and Gain Score. The result showed there were significant differences in learning outcomes between students who used modules and students who used conventional methods with a significance level of 0.005 and project-based learning modules as a source of learning for vocational students to prove effective enough to improve student learning outcomes in Productive Multimedia subjects with a gain score of 0,669 which was classified as medium category.